Offender Reintegration in South Africa during the Covid-19 Pandemic: Criminological Perspective - Ernest Ramokone Lekalakala; Kholofelo Annah Rakubu (E-Journal of Humanities, Arts and Social Sciences)
The former Minister of Correctional Services, Ronald Lamola, announced the early release of 19,000 inmates on parole as a measure to mitigate the impact of the COVID-19 pandemic within South African correctional facilities. This decision aimed to reduce overcrowding, which posed a significant challenge to implementing preventative measures such as social distancing among inmates and staff. Low-risk offenders were prioritised for release to ensure compliance with lockdown regulations. Consequently, communities were deprived of the opportunity to deliberate on the reintegration of released offenders. Drawing on criminological theories and qualitative data collected from 30 purposefully selected participants—including 15 released offenders (10 males and 05 females), 10 community leaders, and 05 personnel from the Department of Correctional Services—this study examined the ramifications of early inmate release, focusing on community rejection and its potential to exacerbate recidivism rates. The study argued that the rejection experienced by prematurely released offenders may result in frustration, heightening the likelihood of re-offending. Furthermore, it is posited that post-pandemic South Africa may witness an increase in crime rates, with this research exploring the nature of offences likely to be committed by rejected parolees. The findings contribute to criminological scholarship by offering empirical insights into the socio-economic and psychological challenges faced by parolees post-early release. Additionally, the study advanced discussions on correctional policy by highlighting the necessity of community engagement in offender reintegration to mitigate recidivism. The study’s findings have implications for both policymakers and practitioners, highlighting the importance of structured post-release support systems to facilitate successful reintegration.